Produção de vetores recombinantes para análise das propriedades biológicas e cancerígenas da proteína K1 do herpesvírus associado ao sarcoma de Kaposi (KSHV/HHV-8) - Squiavinato, Annie Cristhine Moraes Sousa [UNESP] (2014)
Kaposi's sarcoma-associated herpesvirus (KSHV) is a gammaherpesvirus associated with the development of Kaposi's sarcoma. The K1 protein of KSHV has been shown to induce increases the survival and proliferation of infected cells. The viral ORF-K1 shows high variability, so it is possible to distinguish different KSHV genotypes (genotypes A, B, C, D). So far, it is unclear whether different viral genotypes have their own biological characteristics. To this intent, recombinant vectors were generated containing the ORFK1 genotypes A and B. ORF-K1 was obtained from the DNA of primary effusion lymphoma (PEL) cell lines. The amplicon generated and the commercial vector were digested, bonded and cloned in E.coli DH5α. Selected clones underwent automated DNA sequencing. The generated sequences were compared with prototype sequences of ORF-K1. The amino acid sequences from vectors were generated and analyzed in the K1 ITAM-coding region. Validated clones were stably transfected into HEK293 cells and K1 expression was evaluated using Western blot (WB). DNA sequencing showed that the ORF-K1 recombinant vectors corresponds to the prototype sequences deposited from PEL cell lines. WB demonstrated the presence of K1 in the lysate of HEK293 transfected cells. Analysis of the K1 amino acid sequence encoded in the vectors revealed that ITAM domain of K1 (genotype B) has distinct amino acids from the ones in the ITAM domain of K1 (genotypes A and C). Therefore ORF-K1 recombinant vectors were produced and validated, and will be useful to establish an experimental model for analysis of the biological properties of the K1 protein